HUBUNGAN TINGKAT PENGETAHUAN DENGAN KEPATUHAN BEROBAT DI KLINIK PROGRAM TERAPI RUMATAN METADON DI PUSKESMAS PARAKAN KABUPATEN TEMANGGUNG - Sari Dwi Martiani; Heni Lutfi Yati; Tiara Mega K (Pharmaciana, 2016)
Psycho active substance abuse is a common problem throughout the world, and it is associated with the increase of mortality and morbidity. One of substitution therapy program is methadone maintenance therapy program. The main problem is most of patients stop following the maintenance program before they feel the therapeutic effects of it. Compliance in taking daily medication is the focus in achieving the health status of patients. The research objective is to determine the relationship between the knowledge level with methadone maintenance therapy program in the public health center of Parakan, District of Temanggung. The research method was cross sectional approach. The population in this study were all patients of methadone maintenance therapy program in the public health centers of Parakan, District of Temanggung. Samples on this research were 31 patients and they are all active on methadone maintenance therapy program in the public health center of Parakan, District of Temanggung. Data analysis was performed using Chi Square (x2) formula correlation test. The results show there is a relationship between knowledge level with methadone maintenance therapy program in the public health center of Parakan, District of Temanggung with p value 0.001, with 13 respondents (42%) are in a good level of knowledge category and methadone treatment in obidiance catagory is 11 respondents (35.5%). It is concluded that there is a relationship between methadone maintenance therapy program in the public health center of Parakan, District of Temanggung.